2004
DOI: 10.1152/ajpgi.00018.2004
|View full text |Cite
|
Sign up to set email alerts
|

Chronic alcohol consumption accelerates liver injury in T cell-mediated hepatitis: alcohol disregulation of NF-κB and STAT3 signaling pathways

Abstract: Alcohol consumption is a major risk factor accelerating the progression of liver disease in patients with chronic hepatitis virus infection. However, the mechanism underlying the enhanced susceptibility of alcoholics to liver injury is not fully understood. Here, we demonstrate that chronic ethanol consumption increases the susceptibility of C57BL/6 mice to concanavalin A (Con A)-induced T cell-mediated hepatitis. Injection of a low dose of Con A (5 microg/g) causes severe liver damage in ethanol-fed mice as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 51 publications
5
43
0
Order By: Relevance
“…It is also known that the NFB and MAPK pathways, including p38 and JNK, participate in HSC activation [45,46,47]. Therefore, we treatment of rats, and ongoing production of proinflammatory cytokines regulated by NFB is believed to play a major role in CCl 4 -induced liver fibrosis [48,49,50]. The key feature of liver fibrosis is the increase in collagen type I synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that the NFB and MAPK pathways, including p38 and JNK, participate in HSC activation [45,46,47]. Therefore, we treatment of rats, and ongoing production of proinflammatory cytokines regulated by NFB is believed to play a major role in CCl 4 -induced liver fibrosis [48,49,50]. The key feature of liver fibrosis is the increase in collagen type I synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated an essential role for NF-jb activation in Con A-induced hepatitis [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…increased maturation, cytokine and chemokine secretion) [15,16]. Also, in mice, and in cell culture systems, alcohol affects other cell signaling pathways, such as reduced activation of signal transducer and activator of transcription (STAT)1 and STAT3 [17,18]. Furthermore, products of alcohol metabolism have been linked to autoimmunity (e.g.…”
mentioning
confidence: 99%